Criteria for Rehabilitation and Prevention of Patients with Endogenous Psychoses - Ibragimova Muazam Holdorovna; Xushvaktova Dilnoza Hamidullaevna; Xayatov Rustam Batirbekovich (Peerian Journals Publishing, 2023)
In the review of scientific literature carried out to study the state of psychosocial rehabilitation of patients with mental disorders and behavioral disorders, it was found that this subject area has an important research and organizational and methodological direction in psychiatry, has become an important part of the content of psychiatric care to the population. The obtained result of the scientific analysis of the subject area can be used in the practical activities of medical specialists in the organization of psychiatric care to the population, to compile educational programs to improve the professional qualifications of psychiatrists and medical psychologists. The review substantiates the relevance and novelty of research directions for further development of the problem of improving the organization and content of psychiatric care for patients with mental disorders and behavioral disorders.
Keywords: endogenous psychoses; schizophrenia; rehabilitation